Vibration Adjuvant Wound Therapy Enchances The Healing Of Diabetic Foot Ulcers: An Interim Analysis Of 31 Patients - Syabariyah, Sitti; Nurachmah, Elly (Jurnal Keperawatan dan Kesehatan, 2015)
Introduction: Diabetic foot ulcer (DFU) is a common complication of diabetes mellitus and remains a major global public health problem and a great challenge in the realm of clinical nursing care. Previous studies suggested that vibration can improve skin blood flow. However, there was no evidence to suggest that vibration had an effect on diabetic wound healing. Objectives:This study is to establish whether vibration therapy, as an adjunct to standard wound care, can significantly improve the healing of diabetic foot ulcers.  Methods:In this prospective experimental study thirty one patients with grade I-III Wagner Grading of DFU in Sudarso General Hospital, Pontianak and Ade Muhammad Djoen General Hospital, Sintang, West Borneo, Indonesia, were randomly assigned to experimental group (EG, received standard wound care and vibration therapy, n = 16) and control group (CG, received standard wound care alone, n = 15). Results:There were significant differences in total duration of wound care between EG (21.12?10.86 days) and CG (41.47?18.61 days) (P = .04). There were also differences in percentage of wound healing as a function of time. By the end of week 2, percentage of wound healing in EG was 25% while in CG it was nil (P = .038). By the end of week 3, percentage of wound healing in EG was 50% while in CG it was 13.3%, (P = .029). By the end of week 4, percentage of wound healing in EG was 100% while in CG it was 66.7%, (P = .012). Conclusions:The findings of the present study shows that vibration therapy, as an adjunct to standard